1997
DOI: 10.1099/0022-1317-78-11-3045
|View full text |Cite
|
Sign up to set email alerts
|

The 3' untranslated region of alfalfa mosaic virus RNA3 contains a core promoter for minus-strand RNA synthesis and an enhancer element.

Abstract: The 3h untranslated regions (UTRs) of the three genomic RNAs of alfalfa mosaic virus consist of a 3h homologous sequence of 145 nt and upstream unique sequences 18-34 nt in length. Mutations were made in the 3h UTR of a cDNA clone of RNA3. Point mutations in five AUGC motifs which interfere with specific binding of coat protein to the 3h UTR had no effect on template activity of RNA3 for minus-strand RNA synthesis in vitro by purified viral RNA-dependent RNA polymerase (RdRp). Deletion analysis showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Replication enhancers have been reported for several RNA viruses, including Alfalfa mosaic virus (36), Turnip crinkle virus (26), and bacteriophage Q␤ (1). Similarly, region III of TBSV has been shown to exhibit enhancer-like properties typical of DNA transcriptional enhancers, including the ability to (i) increase basal levels of DI RNA accumulation significantly (by ϳ10-fold); (ii) function independently of orientation; and (iii) retain activity at different positions (32).…”
mentioning
confidence: 99%
“…Replication enhancers have been reported for several RNA viruses, including Alfalfa mosaic virus (36), Turnip crinkle virus (26), and bacteriophage Q␤ (1). Similarly, region III of TBSV has been shown to exhibit enhancer-like properties typical of DNA transcriptional enhancers, including the ability to (i) increase basal levels of DI RNA accumulation significantly (by ϳ10-fold); (ii) function independently of orientation; and (iii) retain activity at different positions (32).…”
mentioning
confidence: 99%
“…It has been found that addition of a poly(A) tail to the 3Ј ends of the AMV RNAs partially replaces the requirement for CP in the inoculum (13). Moreover, binding of CP to the 3Ј untranslated regions (UTRs) of RNAs 3 and 4 strongly enhanced translation of these RNAs (13; L. Neeleman, H. J. M. Linthorst, and J. F. Bol, submitted for publication).AMV RNAs are flanked by 5Ј and 3Ј UTRs that are highly structured and presumed to contain cis-acting elements involved in translation and replication (14,15,22,23,24,25,27,28). The 3Ј UTRs of the three RNAs consist of a common 3Ј-terminal sequence of 145 nucleotides (nt) preceded by 18 to 34 nt that are unique for each RNA.…”
mentioning
confidence: 99%
“…AMV RNAs are flanked by 5Ј and 3Ј UTRs that are highly structured and presumed to contain cis-acting elements involved in translation and replication (14,15,22,23,24,25,27,28). The 3Ј UTRs of the three RNAs consist of a common 3Ј-terminal sequence of 145 nucleotides (nt) preceded by 18 to 34 nt that are unique for each RNA.…”
mentioning
confidence: 99%
“…These RNA replication enhancers, which can be found in both plus and minus strands of viral RNAs, are located at variable positions in relation to the initiation site for RNA transcription and are thought to facilitate the recruitment of RdRp to the template (17). Replication enhancers have been characterized for a number of RNA viruses such as bacteriophage Q␤ (2), Alfalfa mosaic virus (46), Tomato bushy stunt virus (37), Brome mosaic virus (10,35,36), and Sindbis virus (11).…”
mentioning
confidence: 99%